2022
DOI: 10.3390/ph15010062
|View full text |Cite
|
Sign up to set email alerts
|

Testing Mitochondrial-Targeted Drugs in iPSC-RPE from Patients with Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly. No universally effective treatments exist for atrophic or “dry” AMD, which results from loss of the retinal pigment epithelium (RPE) and photoreceptors and accounts for ≈80% of all AMD patients. Prior studies provide evidence for the involvement of mitochondrial dysfunction in AMD pathology. This study used induced pluripotent stem cell (iPSC) RPE derived from five AMD patients to test the efficacy of three drugs (AICAR (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…After acute and extended drug exposure, the mitochondria of the RPE were analysed and the results showed differential responses to the drugs across patient lines. 86 This study shows the need for a personalised medicinal approach, and supports the feasibility of using iPSC-derived RPE to develop a personalised drug treatment plan for patients with AMD.…”
Section: Modelling Complex Disease: Age-related Macular Degenerationsupporting
confidence: 67%
See 1 more Smart Citation
“…After acute and extended drug exposure, the mitochondria of the RPE were analysed and the results showed differential responses to the drugs across patient lines. 86 This study shows the need for a personalised medicinal approach, and supports the feasibility of using iPSC-derived RPE to develop a personalised drug treatment plan for patients with AMD.…”
Section: Modelling Complex Disease: Age-related Macular Degenerationsupporting
confidence: 67%
“…More recently, a study used iPSC‐derived RPE from AMD patients to test the efficacy of three mitochondrial maintenance drugs: AICAR (5‐Aminoimidazole‐4‐carboxamide ribonucleotide), Metformin, and Trehalose. After acute and extended drug exposure, the mitochondria of the RPE were analysed and the results showed differential responses to the drugs across patient lines 86 . This study shows the need for a personalised medicinal approach, and supports the feasibility of using iPSC‐derived RPE to develop a personalised drug treatment plan for patients with AMD.…”
Section: Modelling Complex Disease: Age‐related Macular Degenerationsupporting
confidence: 55%
“…iPSC-RPE cells derived from AMD patients have been established to test the efficacy of drugs in AMD. Three AMPK activators AICAR (5-Aminoimidazole-4-carboxamide ribonucleotide), metformin, trehalose, have been tested for maintaining mitochondrial function in AMD iPSC-RPE cells (Ebeling et al, 2022). Rapamycin is a drug used to prevent organ transplant rejection.…”
Section: Resveratrolmentioning
confidence: 99%
“…New drug targets and drug candidates, more preclinical and clinical studies are also needed to test their efficacy and safety for RPE degeneration and AMD. Work on AMD-derived iPSC-RPE cells has shown considerable variability in drug response across patient cell lines (Ebeling et al, 2022). Therefore, a personalized medicine approach, including stratifying patients based on genotyping and more clinically relevant features, is needed in the future.…”
Section: Conclusion Marks and Future Directionsmentioning
confidence: 99%
“…Furthermore, a study by Ebeling et al that analyzed the influence of metformin on individual patient-derived RPE cell lines indicated that the effect of metformin was not uniform across all patients. The group suggests that patient-specific responsiveness to metformin should be taken into account before prescription and that approaches toward personalized medicine are necessary [50].…”
Section: Limitations Of Metformin Usementioning
confidence: 99%